Global Forum on Transparency and Exchange of Information for Tax Purposes Peer Reviews: Lesotho 2016 Phase 2: Implementation of the Standard in Practice (Global Forum on Transparency and Exchange of Information for Tax Purposes, 2016)
This report contains the 2014 "Phase 2: Implementation of the Standards in Practice" Global Forum review of Lesotho. The Global Forum on Transparency and Exchange of Information for Tax Purposes is the multilateral framework within which work in the area of tax transparency and exchange of information is carried out by over 130 jurisdictions which participate in the work of the Global Forum on an equal footing. The Global Forum is charged with in-depth monitoring and peer review of the implementation of the standards of transparency and exchange of information for tax purposes. These standards are primarily reflected in the 2002 OECD Model Agreement on Exchange of Information on Tax Matters and its commentary, and in Article 26 of the OECD Model Tax Convention on Income and on Capital and its commentary as updated in 2004, which has been incorporated in the UN Model Tax Convention. The standards provide for international exchange on request of foreseeably relevant information for the administration or enforcement of the domestic tax laws of a requesting party. "Fishing expeditions" are not authorised, but all foreseeably relevant information must be provided, including bank information and information held by fiduciaries, regardless of the existence of a domestic tax interest or the application of a dual criminality standard. All members of the Global Forum, as well as jurisdictions identified by the Global Forum as relevant to its work, are being reviewed. This process is undertaken in two phases. Phase 1 reviews assess the quality of a jurisdiction’s legal and regulatory framework for the exchange of information, while Phase 2 reviews look at the practical implementation of that framework. Some Global Forum members are undergoing combined – Phase 1 plus Phase 2 – reviews. The ultimate goal is to help jurisdictions to effectively implement the international standards of transparency and exchange of information for tax purposes